Performing the Sacred - Bino, Carla M. (Studies in Religion and the Arts Ser., 2022)
Intro -- Contents -- Preface -- Figures and Tables -- Figures -- Tables -- Notes on Contributors -- Introduction -- 1 The Drama of Christian Images: Art, Liturgy, Sacred Theatre -- 1 Art, a Sign of Salvation -- 2 Jesus and Art -- 3 The Sacraments as Images -- 4 Rite as Image -- 5 Liturgy as Theatre -- 6 Awaiting Transformation -- 2 A 'Dramatic Turn': The Revolution of Christian Representation -- 1 The Show: 'Seeing from Afar' -- 2 The Dramatic Turn: Seeing Up Close -- 3 Conclusion: The Spectacula Christianorum between Memory and Mimesis -- 3 No Drama Please, We're Greek: Sacred Plays from a Greek Orthodox Perspective -- 1 Hellenistic Jews and Antitheatrical Culture -- 2 Enter the Archbishop -- 3 The Service of the Furnace -- 4 Conclusion -- 4 Enacting Sacred Narrative: Biblical, Liturgical, and Sacramental Practices in the Latin West -- 1 The Notions of 'Liturgical Drama' and 'Sacrament' -- 2 The Fleury Raising of Lazarus -- 5 Mary in the Scriptures as Container and Way: Henry Adams and the Virgin of Chartres -- 6 The Power of Images of Passion: Animated Sculptures of the Crucified Christ -- 7 Women as Performers of the Bible: Female Preaching in Premodern Europe -- 1 Introduction -- 2 Women and Preaching in Premodern Europe -- 3 Tommasina Fieschi (ca. 1448-1534) Preaching in Private -- 4 Juana de la Cruz (1481-1534) -- 5 María de Santo Domingo (1486-ca. 1524) -- 6 Stefana Quinzani (1457-1530) -- 7 Conclusion -- 8 Dramatic Action and the Participatory Spectator at the Sacro Monte di Varallo: Frozen Theatre -- 1 The Sacro Monte as Immersive Installation -- 2 Activation -- 3 Self-Referential Politics of Space -- 4 De-centering -- 5 Conclusion -- 9 The Paradox of the Saint Actress: Church and Commedia Dell'Arte during the Counter-Reformation -- 1 Church, Theatre, and Performance: A Complex Relationship -- 2 The Fascination of the Stage.